Maternal Knowledge, Involvement and Integrative Early Child Development Programs in Ethiopia - Zewdie, Teka (The Ethiopian Journal of Education, 2021)
This is an exploratory study of maternal behaviors with particular reference to knowledge and levels of involvement in child development. Two groups of mothers representing the high and low class families of two communities in Addis Ababa were compared on PARI (Parental Role, Knowledge and Involvement) Scale in a quasi-experimental fashion. The analyses employed descriptive, correlational parametric and non-parametric procedures, and major maternal socio-demographic characteristics such as education, income and general life conditions were seen against perceived maternal knowledge, and level of involvement in child development. The study revealed significant differences as well as relationships, where perceived maternal knowledge and involvement levels in child development appeared to be primarily dependent on maternal educational and socioeconomic variables. The results appear to be telling more about the differential perception of parental knowledge and roles in child development, as a result of educational and socio-economic disparities. The tendency of especially the low-income group of mothers to show low level of knowledge and low involvement in their children’s development, apparently as a result of the above material and nonmaterial constraints, suggests the use of an integrated approach if the purported programs of early childhood developmental intervention have to realistically meet their objectives